Prenatal diagnosis of left coronary artery to right ventricle fistula. Issue 2 (10th July 2014) - Oztunc, Funda; Gokalp, Selman; Yuksel, Mehmet Aytac; Imamoglu, Metehan; Madazli, Riza
ABSTRACT Prenatal diagnosis of a congenital coronary artery fistula between the left coronary artery and the right ventricle was established at 28 weeks of gestation. Hydrops fetalis developed during follow‐up and the baby died on the first day after delivery. It is rare for coronary artery fistulas to become symptomatic during fetal life. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound, 43:129–131, 2015